Jornalismo, narrativas e discursos : um estudo sobre feminicídio no jornal A Gazeta - Mariano, Isabella Silva de Freitas (2019)
This research has as object the narratives built by the newspaper A Gazet about cases of feminicide in Espirito Santo and intend to answer the following questions: what are the discourses produced by the newspaper A Gazeta’s narrative statements about feminicide? How are the victim's different subject positions narrated by the vehicle? We start from the notion that journalism is an important piece for overcoming the problem, since such confrontation requires redefinitions at symbolic and cognitive levels. With this, we seek, first of all, to understand how journalism contributes to the constitution of feminicide as a social problem and, secondly, to collaborate in defining strategies that can reduce the rates of violence against women. Based on the conceptualization of “feminicide”, “narrative” and “discourse” and on the historical contextualization of actions to combat violence against women, we intend to analyze the statements about this issue present in the newspaper A Gazeta. To do so, we take into account the understanding that the media do not mirror what is happening in society, but rather, through their narratives, they focus on the constitution of the social event. Were chosen four narratives on cases of feminicide occurred in Espírito Santo in 2017 and 2018, involving women in different positions of class, gender and race. This analysis was based on Thompson (2011) depth hermeneutics, which defines three main phases for the investigation: socio-historical analysis, discursive analysis and interpretation/reinterpretation. The empirical analysis occurred in the last two phases of this study, in which it was possible to identify the narrative structures of the selected cases, strongly dramatic and closely related to elements present in the literature; and the discourses produced by A Gazeta journalism, very connected to punitive tendencies and criminal law.